A Pestle Analysis of Maritime Piracy and Maritime Security in the Gulf of Guinea - Lawrence Ofosu-Boateng, Dr. Capt. Nana Raymond; Jiping, Zhang (Advances in Social Sciences Research Journal, 2020)
The Gulf of Guinea is a region that that draws a lot of interest to many nations in Latin America, Europe and West Africa. It is because these countries depend on this region for conducting their business. Most of the countries export their products and import other goods through the Atlantic Ocean (Ali, 2017). The discovery of oil in Nigeria led to increased business transaction in this region and thus, the development of the economy. However, it also led to the rise of piracy, which affected the maritime security of the area. Many ships and other sea vessels have been affected by the acts of pirates who attack the ships and steal the content being transported. Sometimes they could also hijack these vessels and demand for ransom for them to be released. The ability to counterattack the pirates and robberies in this region is affected by factors which range from political, economic, social, technological, legal, and environmental. Matters such weak governments and poor implementation of the laws and conventions make the countries in the region to lack ability to tackle pirates in the sea and thus have to rely on the international security agencies like Interpol policing and other forces to help in providing security in the sea (Hasan, & Hassan, 2016). Increase in population, lack of unemployment, and poverty are also some of the things which makes many youths in the region to participate in these criminal activities because they lack something constructive, which can generate income.